Perlindungan Hukum Tenaga Medis di Rumah Sakit Dalam Perspektif Undang Undang Ketenagakerjaan - Yustinus Rurie Wirawan; Gunawan Widjaja (Jurnal Sosial Teknologi, 2025)
This study aims to describe and analyze legal protection for medical personnel who work in hospitals from the perspective of employment as workers in the health industry. So far, many medical personnel have not been fully aware of their rights as workers or employees of a company, and tend to understand their rights and obligations only from the perspective of the medical profession. This limited understanding is exacerbated by the lack of detailed regulations regarding the rights of medical personnel in Law Number 17 of 2023 concerning Hospitals, which places hospitals as corporate entities in the health industry. This research uses a normative juridical approach by analyzing labor laws and regulations, health regulations, and relevant legal literature. The results of the study show that the legal protection of medical personnel is still not optimal, especially related to normative rights such as working hours, wages, social security, occupational safety and health, as well as industrial relations dispute resolution mechanisms. This condition has the potential to have an impact on the quality of health services and patient safety. This research confirms that strengthening the legal protection of medical personnel is very important to create a safe and professional work environment. One alternative that could be considered is the formation of a medical personnel union, given the success of non-medical unions in championing and protecting the interests of their members collectively.